Enhanced Amelioration of High-Fat Diet-Induced Fatty Liver by Docosahexaenoic Acid and Lysine Supplementations. (25th May 2014) - Lin, Hsin-Yu; Chen, Chih-Chien; Chen, Yu-Jen; Lin, Yuan-Yu; Mersmann, Harry J.; Ding, Shih-Torng
Abstract : Fatty liver disease is the most common pathological condition in the liver. Here, we generated high-fat diet-(HFD-) induced nonalcoholic fatty liver disease (NAFLD) in mice and tested the effects of docosahexaenoic acid (DHA) and lysine during a four-week regular chow (RC)feeding. Our results showed that 1% lysine and the combination of 1% lysine + 1% DHA reduced body weight. Moreover, serum triglyceride levels were reduced by 1% DHA and 1% lysine, whereas serum alanine transaminase activity was reduced by 1% DHA and 1% DHA + 0.5% lysine. Switching to RC reduced hepatic lipid droplet accumulation, which was further reduced by the addition of DHA or lysine. Furthermore, the mRNA expressions of hepatic proinflammatory cytokines were suppressed by DHA and combinations of DHA + lysine, whereas the mRNA for the lipogenic gene, acetyl-CoA carboxylase 1 (ACC1), was suppressed by DHA. In the gonadal adipose tissues, combinations of DHA and lysine inhibited mRNA expression of lipid metabolism-associated genes, including ACC1, fatty acid synthase, lipoprotein lipase, and perilipin. In conclusion, the present study demonstrated that, in conjunction with RC-induced benefits, supplementation with DHA or lysine further ameliorated the high-fat diet-induced NAFLD and provided an alternative strategy to treat, and potentially prevent, NAFLD.